ELT MATERIALS FOR A VOCATIONAL HIGH SCHOOL ENGLISH CLUB: PLANNING AND PRACTICE: Nurdiana - Nurdiana (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
Teaching materials are an important aspect of language teaching. Through teaching materials, students can obtain language input so that their language skills can improve. This research aims to describe teaching materials developed for vocational high schools located in Jakarta. This teaching material was created to be taught to vocational school students during 'English Club' activities. This vocational school has two specializations, namely multimedia and computer network engineering. For this research, three chapters of teaching materials were developed based on a needs analysis questionnaire. 48 students completed the questionnaire. The result is that they need materials that include reading, listening, writing, and speaking skills narrowed down to reading texts related to their major, email writing, and presentation skills. Meanwhile, they need a lot of materials related to English vocabulary, especially those related to their majors. The materials devised were then evaluated by four English teachers whose results were discussed in this study.